Obesity/overweight prevalence and economic burdens by bariatric surgery, metabolic syndrome, and related comorbidity in 2013-2019: a nationwide descriptive analysis - Chong, Kah Suan; Yang, Chun-Ting; Chang, Yi-Hsin; Kuo, Shihchen; Chen, Jian-Han; Lee, Chia-Jung (Audrey); Chang, Erin; Chou, Chu-Kuang; Ou, Huang-Tz (Surgery for obesity and related diseases, 2025)
Existing studies are mainly focused on overall obesity or specific subpopulations, while the disease burden among patients with different characteristics of obesity progression remains uncertain. To conduct a descriptive analysis of the contemporary obesity/overweight associated economic burdens stratified by clinically meaningful features associated with obesity. Utilizing Taiwan’s 2013 National Health Interview Survey and the 2012-2019 National Health Insurance Research Database. Six groups of adults with obesity and/or obesity-related conditions were targeted, including people receiving bariatric surgery (BS, n = 1679), having metabolic syndrome (MS, n = 1437), having body mass index (BMI) ≥27/30 kg/m2 with obesity-related comorbidities (ORCs, n = 1428/552), and having BMI ≥27/30 kg/m2 (n = 3235/1191). Healthcare utilization/expenditures (in 2022 USD) were measured. In the first year of follow-up, the BS group incurred the highest healthcare expenditures ($3494/person), followed by the MS group ($2852), the BMI ≥30/27 kg/m2 with ORCs groups ($2025/$1920), and the BMI ≥30/27 kg/m2 groups ($1160/$1032). In the years following BS, the prevalence and treatments for hypertension, diabetes, hyperlipidemia, and sleep apnea decreased significantly, and healthcare expenditures remained the lowest among the 6 groups but increased gradually. Heterogeneity of geographic distribution of obesity prevalence was observed. Interventions tailored to patient characteristics, especially advanced obesity with high economic burden and obesity-associated geographic disparities, are needed. BS may curtail ORCs/MS, but the gradually increasing expenditures following BS would suggest a need of routine follow-ups. •High costs in patients with bariatric surgery, and comorbid with chronic diseases.•Decline in chronic diseases and associated treatments after bariatric surgery.•Apparent geographic disparities across populations with different obesity status.